Willingness to Communicate in English: An Interview Study with Indonesian Vocational High School Students - Muhammad Yunus; Erfan Efendi; Ronald Ronald; M. Faruq Ubaidillah; Huan Yik Lee (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
Research into willingness to communicate in English has gained momentum in second/foreign language learning recently. Applied linguists have argued for the factors that may hinder learners to communicate in English. However, although extensive studies on willingness to communicate in English have been carried out, the studies have much focused on university and high school students. As a result, very little is known about the hindrances of students' willingness to communicate in English in the context of vocational high schools. To fill such a lacuna, this study was designed to explore hindrances of willingness to communicate in English among Indonesian vocational high school students. In-depth interviews were conducted with 6 participants from three Indonesian vocational high schools with regard to the hindrances they encountered when communicating in English. To analyze the data, we employed Braun and Clarke’s (2006) thematic analysis. Findings from the study suggest four emerging themes: 1) lack of self-confidence, 2) presence of fear, 3) teacher's teaching style, 4) and vocabulary provision. Our study reveals that, even though the participants are aware of the problems, situated supports in the forms of out-of-class English communications are needed to help solve their hindrances in English communications. Pedagogical implications of this study are offered at the end of this article.